Development Strategies of Human Resources in Micro, Small, and Medium Enterprises (MSMEs) in Digitalization Era - Surahmah; Asri Munzilin; Uswatun Chasanah (J-Mabes: Jurnal Manajemen, Akuntansi, Bisnis dan Studi Ekonomi Syariah, 2024)
https://drive.google.com/file/d/1mIOHCrAxQYRcOD6af0dZzBuxKwWRyyFV/view?usp=sharing